An Ergonomic Investigation Pertaining To Work Related Musculoskeletal Disorder Problems Of Industrial Operators In Pressworking Operation - Satgunam, Meenaloshini (2002)
Musculoskeletal disorders (MSDs) occur when there is a mismatch between physical requirements of the job and the physical capacity of the human body. Many manufacturing sector industries, especially workers from heavy industries are facing this kind of problem. MSDs have caused lost workdays, injuries, increased the total costs of workers compensation claims, and decreased employee morale, quality and productivity. Keeping these facts in view, present study was planned and investigations were undertaken, in a manufacturing industry, PHN Industry, Shah Alam, Selangor where a cross-sectional study was carried out on a group of male workers in an automotive factory. The objective of the study was to determine the prevalence of musculoskeletal disorder and its relationship with various work -related and demographic factors.